EVALUASI EFEKTIVITAS PELATIHAN DENGAN MENGGUNAKAN METODE KIRKPATRICK PADA PT. SWABINA GATRA - Tisiya Wardani, Devi; Cahyadi, Nur (MANAJEMEN DEWANTARA, 2024)
The purpose of this study is to find out and evaluate the effectiveness of employee training of PT. Swabina Gatra uses the Kirkpatrick evaluation model which represents the response or measurement of participant satisfaction with the implementation of the training, the learning obtained by the trainees, and changes in participants' behavior at work. The method used in this study is descriptive quantitative research. Data sources for this study were obtained from primary and secondary sources. Primary data was obtained by distributing questionnaires to participants while secondary data was obtained from documents, books, and literature. From the results of the pre-test and post-test, the learning performance increased from the initial average of 64.50 to 82.50, and from 64.50 in the pre-test > 82.50 in the post-test. It can be concluded that learning evaluation has a significant impact on training. The training effect is good, and the trainees are satisfied and have a good feeling about the training. At the behavioral level, the participants were able to apply the knowledge and skills gained, which shows that training has a significant impact on the overall effectiveness of the program